Factors Related to Farmers' Health Seeking Behaviours Following Snake Bite - Ruris Haristiani,; Rismawan Adi Yunanto,; Baskoro Setioputro,; Deskita Prastiwi, (Journal of Islamic Nursing, 2025)
A huge number of mortalities and morbidities of snake-bite is mostly reported from tropical countries in agriculture occupants. The purpose of this study was to determine the factors related of farmers' health seeking behavior following snakebite. The research design used quantitative method with correlational descriptive research with a cross-sectional approach. The type of sampling technique used probability sampling using the cluster sampling method with a total sample of 100 respondents. Data were collected using 6 questionnaires to measure factors related to the behavior of seeking health assistance due to snakebites including knowledge level, perception of illness, attitude, income level, and accessibility of health services. We used Chi square test and Fisher exact test to analyze the data. The result showed that there was a relationship between the level of knowledge (p 0.000), perception of sickness (p 0.003), health service accessibility (p 0.005), income levels (p 0.001), and attitudes (p 0.021) to farmers' health seeking behaviors of snakebite. Based on these findings, it is urgently needed to give health education to farmers related to appropriate health seeking behaviours of snakebite. Keywords: farmers, health-seeking behaviours, snakebite.